Substrate for chemical impregnation
Patent Information
- Application Number
- JP2025057518
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0006】 本発明によれば密度が低く、薬液含浸速度が速く、かつ基材に一定の固さがあり、薬液含浸時の取り扱いがしやすい、薬液含浸用基材を提供することができる。
Smart Images

Figure 2026165237000001
Abstract
Description
[Technical Field]
[0001] The present invention relates to a chemical impregnation substrate used for impregnating and retaining evaporative agents and releasing them into the air at room temperature, and more specifically, to a chemical impregnation substrate with excellent liquid absorption properties for chemicals intended for insecticidal, sterilizing, insect repellent, pest repellent, fragrance, deodorizing, etc. [Background technology]
[0002] Substrates for chemical impregnation are used in suction-type liquid fragrances and deodorizers to draw up the chemical solution from the container and replenish the substrate while simultaneously volatilizing the chemical from the substrate into the atmosphere. They are also used as indicators to show the remaining shelf life in insecticides, deodorizers, and the like. The indicator is designed so that a display appears indicating the end of the effective period as the chemical solution decreases due to evaporation. When adding an indicator function to a chemical solution-impregnated substrate, since the chemical solution is not supplied over time, various proposals have been made regarding the liquid absorption performance of the chemical solution-impregnated substrate and the addition of the indicator function in order to achieve the target chemical effect and the effective period of the indicator function. Patent Document 1 describes a material containing both mercerized pulp and unmercerized pulp, with an unmercerized pulp content of 30-90% by mass and a density of 0.30-0.38 g / cm³. 3 A base paper with an internal bonding strength of 50 mJ or more has been proposed. It has been explained that the use of mercerized pulp can yield a base paper that is bulky, low-density, and has a high chemical impregnation rate. Patent Document 2 describes a chemical-impregnated substrate in which, when a chemical solution is dropped onto the surface of the chemical-impregnated substrate, the absorption of the chemical solution into the chemical-impregnated substrate and diffusion onto the surface of the chemical-impregnated substrate are good. The substrate consists of two layers, a first layer and a third layer, mainly composed of cellulose fibers, with a second layer made of cellulose fibers and synthetic fibers laminated between them. The blending ratio of cellulose fibers to synthetic fibers in the second layer is 20-80:80-20% by weight, the cellulose fibers contain at least 50% by weight of mercerized pulp or cotton linter pulp, the synthetic fibers consist of main fibers and binder fibers, the blending ratio of main fibers to binder fibers is 20-80:80-20% by weight, the layer ratio of the first, second, and third layers is 45-35:30-10:45-35% by weight, and the basis weight of the chemical-impregnated substrate is 75-500 g / m². 2 Furthermore, the density is 0.25-0.50 g / cm³. 3 Something has been proposed. However, in terms of productivity in the chemical impregnation process, further improvement in production speed is required, and the chemical absorption rate of the substrates proposed in these cases was insufficient. If the density of the substrate is further reduced to increase the chemical absorption rate, the substrate will break during the chemical impregnation process due to insufficient strength. A substrate that has sufficient strength for the production process while improving the chemical absorption rate is needed. [Prior art documents] [Patent Documents]
[0003] [Patent Document 1] Japanese Patent Publication No. 2018-168514 [Patent Document 2] Japanese Patent Publication No. 2015-193954 [Overview of the project] [Problems that the invention aims to solve]
[0004] Conventionally, in order to improve productivity, the use of mercerized pulp and cotton linters has been proposed for chemical impregnation substrates (hereinafter also referred to as substrates) used in indicators and other devices impregnated with chemical solutions. However, these proposed substrates were insufficient to meet the required absorption rate of the chemical solution, and improvements were needed. Furthermore, in order to improve chemical impregnation, it was necessary to reduce the density of the substrate, and the selection of fibers to be used as raw materials was a challenge. The present invention aims to provide a chemical impregnation substrate that is bulky (low density), absorbs chemicals quickly, has a certain degree of hardness, and is easy to handle when impregnated with chemicals. [Means for solving the problem]
[0005] In view of the above problems, we have found that these problems can be solved by blending kraft pulp and sulfite pulp as wood pulp and incorporating rayon fibers, and have completed the present invention. Specifically, the present invention provides the following. (1) A base material for chemical impregnation, which is a single-layer or multi-layer paper containing wood pulp and rayon fibers, characterized in that the rayon fibers are contained in an amount of 10% by weight or more and 40% by weight or less relative to the wood pulp. (2) The chemical impregnation substrate according to (1), characterized in that the wood pulp consists of kraft pulp and sulfite pulp. (3) The ratio of kraft pulp to sulfite pulp in the wood pulp is kraft pulp:sulfite A chemical impregnation substrate according to (1) or (2), characterized in that the pulp ratio is 55:20 to 25:50. (4) A chemical impregnation substrate according to (1) or (2), characterized in that the bending resistance value measured in accordance with JIS P8125-1:2017 is 700 mN or more. (5) A chemical impregnation substrate according to (1) or (2), characterized in that its density is 0.5 g / cm³ or less. [Effects of the Invention]
[0006] According to the present invention, it is possible to provide a substrate for chemical impregnation that has low density, a fast chemical impregnation rate, a certain degree of hardness, and is easy to handle during chemical impregnation. [Modes for carrying out the invention]
[0007] • Substrate for chemical impregnation The chemical impregnation substrate of the present invention is a single-layer or multi-layer paper having at least one paper layer made from a slurry of wood pulp and rayon fibers mixed in a predetermined ratio as papermaking raw material, and can be manufactured using a paper machine used in known papermaking applications.
[0008] • Wood pulp Wood pulp can be made from wood pulp such as softwood pulp or hardwood pulp, and one or more of these types can be used. As pulp, it is possible to use a known blend of pulps as appropriate, such as chemical pulps made from wood, including bleached kraft pulp (NBKP) from softwood, unbleached kraft pulp (NUKP) from softwood, bleached kraft pulp (LBKP) from hardwood, unbleached kraft pulp (LUKP) from hardwood, and sulfite pulp (SP); mechanical pulps made from wood, including gland pulp (GP), refiner gland pulp (RGP), stone gland pulp (SGP), chemigland pulp (CGP), semi-chemical pulp (SCP), thermomechanical pulp (TMP), and chemothermetic pulp (CTMP); and recycled paper pulp, which is made from recycled paper and has had the ink removed in a deinking process. Among these, bleached and unbleached kraft pulp and sulfite pulp can be used. As for bleached and unbleached kraft pulp, NBKP and NUKP, which are made from softwood chips, are preferable because the pulp fibers are long and strong, and there is no fiber shedding during the manufacturing process.
[0009] In this invention, it is preferable to use softwood pulp with relatively long fibers or sulfite pulp with high bulk as the wood pulp used to ensure the required air permeability of the base material, and these may also be used in mixture form. Furthermore, when using wood pulp such as softwood pulp or sulfite pulp, each pulp may be beaten individually before being mixed, or multiple pulps may be mixed and then beaten (called mixed beating) before use. In addition, since hardwood pulp has a relatively short fiber length and is prone to shedding during the papermaking process, it is preferable to use a smaller amount of hardwood pulp than softwood pulp.
[0010] • Sulfite pulp (dissolving pulp) Sulfite pulp, a type of wood pulp according to the present invention, is a cellulose raw material obtained by steaming wood chips or non-wood raw materials at high temperature and pressure with a sulfurous acid solution (acidic sulfite, bisulfite, sulfite solution), selectively removing hemicellulose and lignin from the lignocellulose material contained in the wood chips. The proportion of α-cellulose in the sulfite pulp of the present invention is not particularly limited, but is preferably 80% by weight or more, and more preferably 92% by weight or more. The proportion of α-cellulose is measured from its insolubility in a 17.5% aqueous sodium hydroxide solution. Sulfite pulp is preferable because it tends to have a low density when unbeaten. The raw material chips for sulfite pulp are not particularly limited and may be wood (coniferous trees, hardwoods, etc.) or non-wood (plants such as kenaf, bagasse, and bamboo). Sulfite pulp may be produced by an acidic sulfite pulping method or by an alkaline pulping method, but pulp produced by an acidic sulfite pulping method is preferably used.
[0011] • Dilution rate of wood pulp The freeness of the pulp used as wood pulp is preferably 700 ml or more, and the pulp may be unbeaten. The freeness referred to herein is the Canadian Standard Freeness measured in accordance with JIS P8121-2:2012, and is a value measured for each pulp. A substrate produced by papermaking using wood pulp beaten to a freeness of less than 700 ml is difficult to reduce in density and has small voids in the substrate, so that the chemical impregnation rate may not meet the target.
[0012] ·Blending of kraft pulp and sulfite pulp in wood pulp The blending ratio of kraft pulp and sulfite pulp in the wood pulp is preferably softwood kraft pulp : sulfite pulp = 55:20 to 25:50, more preferably 47.5:27.5 to 32.5:42.5. Within the above range, the density will be an appropriate value, the liquid absorption time will be short, and the hardness of the substrate will also be a suitable value.
[0013] ·Other additives If necessary, other additives can be internally added to the paper substrate. Examples of the additives include fillers, pigments, sizing agents, coagulants, fluorescent brighteners, aluminum sulfate, retention aids, freeness improvers, dry paper strength enhancers, wet paper strength enhancers, color dyes, color pigments, water resistance agents and the like, which can be used alone or in combination of two or more.
[0014] ·Rayon fiber Rayon fibers are produced by dissolving cellulose such as pulp and cotton linters in an alkali such as sodium hydroxide and carbon disulfide to form viscose, followed by spinning in an acid (wet spinning). In the present invention, wood pulp and rayon fibers can be contained, and the blending amount of the rayon fibers relative to all papermaking fibers is 10% by weight or more and 40% by weight or less. When the blending amount of rayon fibers is less than 10% by weight, it may be difficult to obtain the predetermined density (bulkiness) and liquid absorbency. When the blending amount of rayon fibers exceeds 40% by weight, the operability may be deteriorated, for example, fibers fall off from the paper substrate sheet during papermaking and cause machine contamination. The fineness of the rayon fibers is preferably 0.3 to 7.0 dtex, more preferably 0.5 to 5.0 dtex, and even more preferably 0.8 to 4.0 dtex. When the fineness of the rayon fibers is equal to or greater than the lower limit value within the aforementioned numerical range, the sheet strength tends to improve. When the fineness of the rayon fibers is equal to or less than the upper limit value within the aforementioned numerical range, the dispersibility of the chemical fibers in the slurry during nonwoven fabric production tends to improve. The fineness of the chemical fibers is measured in accordance with JIS L-1015:2010. The average fiber length of the rayon fibers is preferably 3 to 20 mm, more preferably 3 to 15 mm, and even more preferably 3 to 10 mm. When the average fiber length of the chemical fibers is equal to or greater than the lower limit value within the aforementioned numerical range, the sheet strength tends to improve. When the average fiber length of the chemical fibers is equal to or less than the upper limit value within the aforementioned numerical range, the chemical fibers are less likely to get entangled in the production equipment, facilitating nonwoven fabric production. The average fiber length of the chemical fibers is measured in accordance with JIS L-1015:2010.
[0015] The paper substrate of the present invention may be a single-layer paper or a multi-layer paper. In the case of a multi-layer structure, at least one layer contains wood pulp and rayon fibers as papermaking fibers, and the content of the rayon fibers is 10 wt% or more and 40 wt% or less relative to the papermaking fibers. In the case of multi-layer paper, the stock constituting each layer may be the same or different, but it is preferable that all paper layers satisfy the aforementioned specific formulation.
[0016] The basis weight of the substrate is not particularly limited and can be appropriately selected depending on the application, but it is 80 g / m 2 or more, and further can be 120 g / m 2 or more. When the basis weight is less than 80 g / m 2 , breakage may occur in the liquid absorption step due to a decrease in wet tensile strength, or the desired liquid absorption capacity may not be achieved. In addition, the basis weight is preferably 120 g / m 2 or more, but when the basis weight is higher than 180 g / m 2 , the volatility of the absorbed chemical liquid deteriorates and the effect due to chemical liquid volatilization may decrease. Therefore, the upper limit of the basis weight is preferably adjusted as appropriate in consideration of the cost, the chemical liquid to be used, and the target service life (volatility).
[0017] The strength of the paper substrate is preferably such that the longitudinal tensile strength, measured in accordance with JIS P8113:2006, is 2.0 kN / m or higher, and more preferably 2.5 kN / m or higher. If the tensile strength is less than 2.0 kN / m, paper breakage may occur during the papermaking process.
[0018] The bending resistance value of the paper substrate, measured in accordance with JIS P8125-1:2017, is preferably 700 mN or more, and more preferably 1000 mN or more. The bending resistance value only needs to be 700 mN or more in either the vertical or horizontal direction. If the bending resistance value is 700 mN or more, it has a certain degree of stiffness, making it easy to handle in the chemical impregnation process. If it is less than 700 mN, it becomes soft and lacks rigidity, causing it to bend when the substrate is sucked up in the chemical impregnation process, making it difficult to suck up.
[0019] (Manufacturing method) The chemical impregnation substrate of the present invention can be manufactured using methods known to be used in papermaking applications. Specifically, it can be manufactured using a long-wire paper machine, a cylinder paper machine, a short-wire paper machine, a twin-wire paper machine, an on-top hybrid paper machine, a gap former machine, or a multi-layer paper machine combining these. Furthermore, additives can be added as needed. For example, fillers, pigments, sizing agents, coagulants, fluorescent whitening agents, aluminum sulfate, yield enhancers, water drainage enhancers, dry strength enhancers, wet strength enhancers, coloring dyes, coloring pigments, water-resistant agents, etc., can be used individually or in combination. While internal addition of these additives is preferred, they can also be applied (externally) through impregnation processes such as mangling and sizing presses, or surface coating using gate roll coaters, blade coaters, bar coaters, gravure coaters, die coaters, curtain coaters, spray coaters, etc. [Examples]
[0020] The present invention will be described below with reference to examples, but the present invention is not limited to the following examples.
[0021] (Example 1) 47.5 wt% of NBKP with a Canadian Standard Freeness (CSF) of 720 ml, 27.5 wt% of sulfite pulp with a Canadian Standard Freeness (CSF) of 754 ml (unbeaten), and 25 wt% of rayon fibers (3.3 dtex × 5 mm, manufactured by Daiwabo Rayon Co., Ltd.) were mixed and stirred to prepare a papermaking raw material. Using this papermaking raw material, the target basis weight was 150 g / m 2 for hand-making paper, and this wet web was dried at a drying temperature of 120°C for a drying time of 2 minutes to obtain a base material.
[0022] (Example 2) A base material was obtained by making paper in the same manner as in Example 1, except that the NBKP content was 40.0 wt% and the sulfite pulp content was 35.0 wt%.
[0023] (Example 3) A base material was obtained by making paper in the same manner as in Example 1, except that the NBKP content was 32.5 wt% and the sulfite pulp content was 42.5 wt%.
[0024] (Comparative Example 1) A base material was obtained by making paper in the same manner as in Example 1, except that the NBKP content was 53.3 wt%, the sulfite pulp content was 46.7 wt%, and no rayon fibers were blended
[0025] (Comparative Example 2) A base material was obtained by making paper in the same manner as in Example 1, except that the NBKP with a Canadian Standard Freeness (CSF) of 655 ml was 50.0 wt% and the rayon fiber content was 50.0 wt%.
[0026] (Comparative Example 3) A base material was obtained by making paper in the same manner as in Example 1, except that the NBKP with a Canadian Standard Freeness (CSF) of 655 ml was 25.0 wt% and the rayon fiber content was 75.0 wt%.
[0027] (Evaluation Methods) (1) Freeness The Canadian Standard Freeness was measured in accordance with JIS P8121-2:2012. (2) Basis Weight The measurement was performed in accordance with JIS P 8124:2011. (3) Thickness Measurements were taken in accordance with JIS P 8118:2014. (4) Density Measurements were taken in accordance with JIS P 8118:2014. (5) Tensile strength Measurements were taken in accordance with JIS P8113:2006. (6) Absorption time The measurement sample was conditioned at 23°C and 50% RH for 24 hours, and a test piece (5cm x 10cm) was prepared from this sample. 40 μl of the pyrethroid compound profluthrin (product name: Fairtail (viscosity 14.1 mPa·s) / manufactured by Sumitomo Chemical Co., Ltd.) was dropped onto the surface of the test piece using a microsyringe, and the time it took for the drug to penetrate into the sample was visually observed. The time from dropping to penetration (absorption time) was measured, and the absorption capacity was evaluated as "○" or "×" as shown below. 〇: Less than 15 seconds ×: 15 seconds or more (7) Bending resistance Measurements were taken in accordance with JIS P8125-1:2017, with a bending angle of 20° and a bending length of 5mm. (8) Number of fibers shed from handmade sheets In the actual papermaking process, fiber shedding from the pulp can lead to machine contamination. To investigate this possibility, the number of detached fibers was measured in a hand-made sheet. Specifically, a handmade sheet was wrapped around the roll of a Hishira copier and rotated for 5 minutes. The number of fibers that fell off was then visually inspected in a 1.8cm x 7.5cm area. ○: Number of shed fibers: Less than 200 ×: Number of shed fibers: 200 or more
[0028] [Table 1]
[0029] ·result According to Examples 1-3, a chemical impregnation substrate, which is a blend of NBKP and sulfite pulp as wood pulp and a certain amount of rayon, exhibits excellent liquid absorption, a certain degree of bending resistance, and good handling and operability during the chemical impregnation process. As can be seen in Comparative Example 1, when the amount of rayon is small (or no rayon is added), the density increases and the liquid absorption time increases. As shown in Comparative Examples 2 and 3, when the amount of rayon is large, the impregnated substrate becomes softer, the bending resistance decreases, and the amount of rayon-derived shed fibers increases, resulting in poor operability during actual production.
Claims
1. It is either single-layer paper or multi-layer paper. It contains wood pulp and rayon fibers. A chemical impregnation substrate characterized by containing 10% to 40% by weight of the rayon fibers relative to wood pulp.
2. The chemical impregnation substrate according to claim 1, characterized in that the wood pulp consists of kraft pulp and sulfite pulp.
3. The chemical impregnation substrate according to claim 1 or 2, characterized in that the content ratio of kraft pulp to sulfite pulp in the wood pulp is kraft pulp:sulfite pulp = 55:20 to 25:
50.
4. A chemical impregnation substrate according to claim 1 or 2, characterized in that the bending resistance value measured in accordance with JIS P8125-1:2017 is 700 mN or more.
5. Density is 0.5 g / cm³ 3 The chemical solution impregnation substrate according to claim 1 or 2, characterized in that it is as follows:
Citation Information
Patent Citations
Chemical-impregnation base material
JP2015193954A
Chemical liquid-impregnated substrate and production method thereof
JP2018168514A